Muestra de Arte Joven 1987. (Madrid : Instituto de la Juventud, 1987)
Alonso, Jesus ; Aymerich, Guillermo ; Barvia, Ignacio ; Berenguer, Carmen ; Blasco, Victor ; Caccamo, Berta ; Cotanda, Ricardo ; Elorrriaga, Javier ; Esteve, Ignasi ; Forrellad, Miquel ; Galindo, Jose ; Guiusado, Sonja ; etc.
Muestra de Arte Joven 1987, Circulo de Bellas Artes, Madrid, 1987
boek